GAMBARAN FORGIVENESS PADA REMAJA AKHIR BROKEN HOME DI KOTA KUPANG - Sarah Marchella Letelay; Marylin Susanti Junias; Christiani Natasya Miru; Mariana Dinah Charlota Lerik (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study was motivated by the high number of parental divorce cases in Kupang City, which affect the psychological condition of late adolescents from broken home families, especially in the process of forgiveness. This study aimed to identify and describe in depth the picture of forgiveness among late adolescents from broken home families due to parental divorce in Kupang City. This study used a descriptive qualitative approach with purposive sampling. The participants were five late adolescents aged 18-22 years from broken home families due to parental divorce. Data were collected through semi-structured interviews and documentation and then analyzed using thematic analysis based on Enright’s four stages of forgiveness: the uncovering phase, the decision phase, the work phase, and the deepening phase. The findings showed that the forgiveness process among participants unfolded gradually, beginning with anger, sadness, and feelings of unfairness, then moving toward acceptance, understanding the reasons behind the divorce, and efforts to reconcile with the situation. In the final stage, participants experienced relief, peace, and greater positive meaning in life. In conclusion, forgiveness among late adolescents from broken home families is a complex yet important psychological process that helps adolescents accept parental divorce experiences and build better emotional well-being. ABSTRAK Penelitian ini dilatarbelakangi oleh tingginya kasus perceraian orang tua di Kota Kupang yang berdampak pada kondisi psikologis remaja akhir dari keluarga broken home, khususnya dalam proses pemaafan atau forgiveness. Tujuan penelitian ini adalah untuk mengetahui dan mendeskripsikan secara mendalam gambaran forgiveness pada remaja akhir broken home akibat perceraian orang tua di Kota Kupang. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik purposive sampling. Partisipan dalam penelitian ini berjumlah lima orang remaja akhir usia 18-22 tahun yang berasal dari keluarga broken home akibat perceraian orang tua. Data dikumpulkan melalui wawancara semi terstruktur dan dokumentasi, kemudian dianalisis menggunakan analisis tematik berdasarkan empat tahap forgiveness menurut Enright, yaitu uncovering phase, decision phase, work phase, dan deepening phase. Hasil penelitian menunjukkan bahwa proses forgiveness pada partisipan berlangsung secara bertahap, diawali dengan kemarahan, kesedihan, dan rasa tidak adil, kemudian berkembang menjadi penerimaan, pemahaman terhadap alasan perceraian, dan usaha untuk berdamai dengan keadaan. Pada tahap akhir, partisipan merasakan kelegaan, ketenangan, serta pemaknaan hidup yang lebih positif. Kesimpulan penelitian ini menunjukkan bahwa forgiveness pada remaja akhir broken home merupakan proses psikologis yang kompleks tetapi penting dalam membantu remaja menerima pengalaman perceraian orang tua dan membangun kesejahteraan emosional yang lebih baik.